Natriuretic peptides: Diagnostic and therapeutic use - Pandit, Kaushik (Medknow Publications & Media Pvt Ltd, 2011)
Natriuretic peptides (NPs) are hormones which are mainly secreted from heart and have important natriuretic and kaliuretic properties. There are four different groups NPs identified till date [atrial natriuretic peptide (ANP), B-type natriuretic peptide (BNP), C-type natriuretic peptide (CNP) and dendroaspis natriuretic peptide, a D-type natriuretic peptide (DNP)], each with its own characteristic functions. The N-terminal part of the prohormone of BNP, NT-proBNP, is secreted alongside BNP and has been documented to have important diagnostic value in heart failure. NPs or their fragments have been subjected to scientific observation for their diagnostic value and this has yielded important epidemiological data for interpretation. However, little progress has been made in harnessing the therapeutic potential of these cardiac hormones.